MONETARY POLICY RULES AS THE FOUNDATION OF THE MODERN PARADIGM OF CENTRAL BANK INDEPENDENCE - Inna O. Shkolnyk; Yurii M. Ohorilko (Academy Review)
The article analyzes the origins of the modern paradigm of central-bank independence both in historical retrospect and from the perspective of the implementation of certain monetary policy rules. The question of central bank independence is one of the main issues in analyzing the foundations of the organization and functioning of these institutions. However, when considering this issue retrospectively, it is impossible not to notice the close connection between central banks’ compliance with monetary policy rules and their actual independence. That is why the research of central-bank independence through the prism of compliance with monetary policy rules is particularly relevant today, especially given the increased discretion in making monetary decisions after the financial crisis of 2008. The authors illustrate that the implementation of monetary policy rules was not a situational or random process. This process was a reaction to the failure of the macroeconomic policy of the 1960s and 1970s, which focused on the Phillips curve as a model for ensuring a low level of unemployment at the expense of high inflation. At the same time, the central bank played a secondary role in the process of macroeconomic stabilization, and its independence was subordinated to the goal of ensuring a stable low level of unemployment. The practice of implementing monetary policy rules (M. Friedman’s rule, J. Taylor’s rule) shows that central banks did not strictly adhere to these prescriptions. Despite this, the authors prove that monetary policy rules, in comparison with the discretionary decisions of central banks, historically give better results in combating high inflation and its volatility. The studied examples of monetary targeting in Germany and Switzerland from the 1970s to the 1990s illustrate the use of monetary policy rules not as a rigid frame, but as a reference point for fixing inflationary expectations of economic agents. At the same time, there is consensus in the scientific literature that the relatively smooth overcoming of exogenous shocks (oil crises, German reunification) in these countries occurred precisely because of the implementation of monetary policy rules. In turn, J. Taylor, whose rule served as a guideline for establishing the optimal interest rate to combat high inflation and ensure economic growth, pointed out that the deviation of central banks from rule-like behavior led to the crisis of 2008, and emphasized the need to return to using monetary rules for macroeconomic stabilization. As a result, the authors concluded that the introduction of monetary policy rules contributed to the elimination of discretion in decision-making and the limitation of political influence on monetary policy. In this case, the effectiveness of monetary policy is not merely linked to the legal consolidation of central-bank independence, but depends on the implementation of monetary policy rules, which form the foundation for the actual independence of monetary institutions.